Learner Perceptions of a Blended-learning Model in Obstetrics and Gynecology Clinical Teaching: A Cross-sectional Program Evaluation - Shuling Zhang; Kuimei Zhang; Xiaoxia Wang; Peipei Zhang; Jiejie Li; Wenming Cao (Research in Health Science, 2026)
We conducted a cross-sectional evaluation of a blended-learning model for obstetrics and gynecology clinical teaching at Changle People's Hospital Affiliated with Shandong Second Medical University. A 12-item five-point Likert questionnaire was completed by 517 learners. Item means ranged from 3.56 to 3.98, and the 12-item composite mean was 3.79 (SD 0.54). The digital competency profile, OSCE/Mini-CEX-oriented assessment, and tutor guidance received the highest ratings, while the 3E flipped-classroom discussion received the lowest. Cronbach's α values ranged from 0.876 to 0.902 across domains and stood at 0.793 for the total scale. An exploratory principal component analysis explained 79.83 per cent of the variance, with the fourth component contributing only 2.72 per cent of the variance. In the multiple linear regression model, these three areas of teaching collectively explained 62.4 per cent of the variance in overall satisfaction. The results indicate that teaching support and assessment feedback showed the strongest independent association with satisfaction (standardised β = 0.789, p < 0.001), whilst online resources and face-to-face activities did not demonstrate an independent association; there was virtually no correlation between online resources and face-to-face exercises (Spearman’s rho = 0.013). Students rated the programme highly overall and rated the feedback-oriented teaching components even more highly, whilst the “3E discussion” component was identified as an area requiring priority improvement.